The cinema in communicative environments. Resilient Adolescence - Rengifo Castillo, Yessika María (Escribanía, 2018)
This article tries to reflect on the role of cinema in non-formal communicative environments. Role that continues to arouse controversy, and more questions than answers. In that sense, it creates a relationship between cinema, education, traditional school, adolescence, and resilience. Creating the possibility of accessing some strategies that promote and strengthen this audiovisual tool, inside and outside the school classrooms. From that perspective, facilitating the understanding of the stage of adolescence that is permeated by physical and psychological changes, which usually determine the actions of young people in different social fields. That is, cinema as a mediator in the educational processes of resilient adolescents, who have gone through events framed by tragedy and are able to continue through strategies such as cinema.